Applications of Unnatural Amino Acids in Protease Probes. Issue 23 (30th October 2019) - Maluch, Izabela; Czarna, Justyna; Drag, Marcin
Abstract: Since proteases are involved in a wide range of physiological and disease states, the development of novel tools for imaging proteolytic enzyme activity is attracting increasing interest from scientists. Peptide substrates containing proteinogenic amino acids are often the first line of defining enzyme specificity. This Minireview outlines examples of major recent advances in probing proteases using unnatural amino acid residues, which greatly expands the possibilities for designing substrate probes and inhibitory activity‐based probes. This approach already yielded innovative probes that selectively target only one active protease within the group of enzymes exhibiting similar specificity both in cellular assays and in bioimaging research. Abstract : Unnatural probes : This Minireview provides a brief summary of the role of unnatural amino acid residues in modulating specificity and/or selectivity of designed probes of proteases.